An intelligent transportation system for smart nations - Sivakumar Niroshinee (Nanyang Technological University, 2023)
Intelligent Transportation Systems (ITS) play a pivotal role in shaping the future of urban mobility. This project harnesses the power of MATLAB to create a sophisticated ITS framework capable of vehicle detection, counting, speed estimation, and image processing. Leveraging advanced computer vision techniques, the system processes video feeds from traffic cameras, accurately detecting vehicles, counting their numbers, and estimating their speeds. Through image segmentation and object recognition algorithms, the system ensures precise analysis, contributing to enhanced traffic management and road safety. MATLAB's computational capabilities enable real-time data processing, providing valuable insights into traffic patterns and facilitating data-driven decision-making. This project demonstrates the potential of MATLAB as a robust tool in the realm of Intelligent Transportation Systems, paving the way for smarter, safer, and more efficient urban transportation networks.